2020
DOI: 10.1016/j.chom.2020.04.008
|View full text |Cite
|
Sign up to set email alerts
|

Combined Prebiotic and Microbial Intervention Improves Oral Cholera Vaccination Responses in a Mouse Model of Childhood Undernutrition

Abstract: Highlights d Mice with microbiota from undernourished children have varied CT vaccine responses d Nutraceutical improves varied vaccine responses to oral CT in gnotobiotic mice d Co-housing mice with responsive (R) and HypoR microbiota improves CT responses d Five bacterial strains plus nutraceutical promotes vaccine efficacy in HypoR animals

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
42
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(42 citation statements)
references
References 42 publications
(42 reference statements)
0
42
0
Order By: Relevance
“…Another report showed that the combination of 2 -fucosyllactose, a dominant oligosaccharide in human milk, long-chain FOS, and short-chain GOS, enhanced the activation of influenza vaccine-specific Th1 cell and B cell activation [139] and increased the levels of IgG1 and IgG2a. Moreover, Luccia et al showed that combined prebiotics (spirulina, amaranth, and flaxseed) and microbial interventions improved the immune responses to CT vaccination in GF mice colonized with the gut microbiota of Bangladeshi nonresponder children [140]. Collectively, these results support the hypothesis that the use of prebiotics may improve vaccine efficacy.…”
Section: Vaccine Efficacy and Gut Microbiotamentioning
confidence: 84%
“…Another report showed that the combination of 2 -fucosyllactose, a dominant oligosaccharide in human milk, long-chain FOS, and short-chain GOS, enhanced the activation of influenza vaccine-specific Th1 cell and B cell activation [139] and increased the levels of IgG1 and IgG2a. Moreover, Luccia et al showed that combined prebiotics (spirulina, amaranth, and flaxseed) and microbial interventions improved the immune responses to CT vaccination in GF mice colonized with the gut microbiota of Bangladeshi nonresponder children [140]. Collectively, these results support the hypothesis that the use of prebiotics may improve vaccine efficacy.…”
Section: Vaccine Efficacy and Gut Microbiotamentioning
confidence: 84%
“…An important caveat underlying our findings is that GF mice lack commensal gut microbes and could have altered immune responses to immunization, especially considering recent studies that have highlighted how V. cholerae-microbiota interactions can influence colonization, disease, and development of anti-V. cholerae immunity [48][49][50][51][52] . However, the strong association of VAT induction with protection and superior efficacy of live over inactivated vaccine strains in this model, and our similar findings of OCV function in mice with transiently disrupted microbiomes reinforces the idea that the GF mouse live OCV model holds substantial translational promise 36,37 .…”
Section: Discussionmentioning
confidence: 99%
“…In gnotobiotic mice model, improved CT-IgA response was observed after colonizing with diet-specific microbiome (Di Luccia et al, 2020 ). In several studies, it was shown that the commensal microbes act as a barrier against enteric pathogens.…”
Section: Influence Of Microbiome On V Cholerae Pamentioning
confidence: 99%